The The Russian Movie T-34: A Duel Between Soldiers and their Tanks - Álvarez, José Maurício Saldanha (Advances in Social Sciences Research Journal, 2023)
The aim of this essay is to exploratory analyze the Russian film Russian War T. 34, by Alexey Sidorov, as a symbolic duel between two individuals, a Nazi German and the other one Soviet, employing their tanks, their backgrounds, their industrial cultures, and ideologies. The Dominant Explain Comes from the Curzio Malaparte reports that, at the beginning of Operation Barbarossa of 1941, advocated Nazi defeat. We use the works of Steve Zaloga to analyze the use of tanks as a combat machines. John Erickson, Brandon Schechter’s reading, explains the victory of the Red Army and the USSR, mobilizing industrial, human, and cultural means employing, according to Lewin, the memory of the Russian victory over Napoleon in 1812. Our Findings indicate that the consolidation of an accelerated industrial mindset produced a new ethics where Tank Crews were soldiers and mechanically inspired and, like an elite, along with industrial technique, employed tricks as a tactic weapon, according to Michel de Certeau. Narrating the dynamic plastic of the battle between tanks, Sidorov’s film holds the viewer’s attention by employing the narrative aesthetics of silent cinema and visualizing his scenes dispensing with the reading of Russian subtitles. The film puts the tank, the top product of the 1930s and 40s celebrated industrial development, as a complex war tool whose employment requires exceptional individuals endowed with cunning and technique of fighting, simultaneously soldiers and mechanical.